2021
DOI: 10.3390/cancers13205124
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Redox Balance Pathway Using Ascorbic Acid in sdhb Zebrafish Mutant Larvae

Abstract: Patients with mutations in the β-subunit of the succinate dehydrogenase (SDHB) have the highest risk to develop incurable malignant phaeochromocytomas and paragangliomas (PPGLs). Therapy development is hindered by limited possibilities to test new therapeutic strategies in vivo. One possible molecular mechanism of SDHB-associated tumorigenesis originates in an overproduction of reactive oxygen species (ROS) due to mitochondrial dysfunction. Ascorbic acid (Vitamin C) has already been shown to act as anti-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In 2021, Dona et al published a Sdhb-KO model in zebrafish which led to loss of complex II activity and elevated succinate levels mimicking the features of SDHB-associated PPGLs in humans [70]. The researchers explored the impact of ascorbic acid on the redox balance of the Sdhb-KO zebrafish larvae, suggesting that the model is a potentially valuable tool to screen for drugs effective against SDHB-associated pseudohypoxic PPGLs [71]. This model opens new possibilities to understand the molecular mechanisms associated to SDHB deficiency, and to investigate novel therapeutic interventions for SDHB-related tumors.…”
Section: Zebrafishmentioning
confidence: 99%
“…In 2021, Dona et al published a Sdhb-KO model in zebrafish which led to loss of complex II activity and elevated succinate levels mimicking the features of SDHB-associated PPGLs in humans [70]. The researchers explored the impact of ascorbic acid on the redox balance of the Sdhb-KO zebrafish larvae, suggesting that the model is a potentially valuable tool to screen for drugs effective against SDHB-associated pseudohypoxic PPGLs [71]. This model opens new possibilities to understand the molecular mechanisms associated to SDHB deficiency, and to investigate novel therapeutic interventions for SDHB-related tumors.…”
Section: Zebrafishmentioning
confidence: 99%
“…In the presence of succinate dehydrogenase, succinate converts into fumarate and reduces FAD to FADH 2 , which donates electrons to the Fe-S clusters, to ultimately be transferred to the reduced ubiquinol form of coenzyme Q [ 122 ] ( Figure 2 B). The dicarboxylate-binding site of complex II (II f site) is associated with electron leakage from ETC and ROS generation [ 123 , 124 ] ( Figure 2 B). In vitro research using isolated mitochondria suggested that the II f sites were reduced after the inhibition of complex II by atpenin A5 in myocardial ischemia [ 123 ].…”
Section: The Role Of Vitamin C In Cardiovascular Pathologiesmentioning
confidence: 99%
“…Alterations in the mitochondrial respiratory chain and redox balance are major pathogenic factors in a subgroup of PPGL. The article by Dona et al presents a novel zebrafish model that could be efficiently used for the study of PPGL [ 16 ].…”
mentioning
confidence: 99%